The economic and political development of African states in the historical context of the decolonization process - Boubacar Sidi Diallo (Czasopismo Prawno-Historyczne)
The study of decolonization has long been dominated by political history, focused on formal emancipation of nations at the turn of the 19th and 20th century, societies subject to European colonial administration. The article reveals the reasons for the emancipation of colonised nations and the construction of a new social and economic order in the world. It also presents the relationship between decolonisation and the new global economic hierarchy. In fact, decolonisation did not change anything in the economic and political relations between former metropolises and former colonies, similarly at the cultural level, where the language of the coloniser still dominates in the official sphere and in education.